Quill mites (Acari: Syringophilidae) from mimid birds (Aves: Mimidae) - Sikora, Bozena; Fajfer, Monika; Skoracki, Maciej (Zootaxa, 2011)
Two new species of syringophilid mites parasitizing birds from the family Mimidae are described: Syringophilopsis mimidus sp. nov. ex Margarops fuscatus (Vieillot) from Central America and Rafapicobia toxostoma sp. nov. ex Toxostoma curvirostre (Swainson) from USA. Additionally, Torotrogla mima Kethley, 1970 is redescribed based on the material ex Mimus triurus (Vieillot) from Argentina and M. patagonicus (Lafresnaye and Orbigny) from South Africa.